2015
DOI: 10.1016/j.mmcr.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenochaeta romeroi causing subcutaneous phaeohyphomycotic cyst in a diabetic female

Abstract: Opportunistic subcutaneous fungal infections are increasing in present times due to increasing incidence of many medical conditions causing immunosupression like diabetes, AIDS, organ transplant recipients and anticancer therapy. Pyrenochaeta romeroi, a fungus from the dematiaceae group, first described by Borelli in 1959, is saprophyte to soil and plants.We present a rare case of subcutaneous phaeohyphomycotic cyst in a diabetic female caused by P. romeroi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…It has mostly been reported in immunocompromised patients receiving immunosuppressive drugs for hematologic malignancy [4], renal transplantation [5], rheumatoid arthritis [6], leprosy [7], and asthma [8]; however, there has been one report of a healthy, immunocompetent host [11], as shown in Table 2. Medicopsis romeroi has also reported in patients with type 2 diabetes mellitus who have poor glycemic control [9,10]. Since phagocytic activity is the main mechanism for anti-fungal infections [12], type 2 diabetes patients with hyperglycemic control have a significant decline in the phagocytic activity of peripheral blood mononuclear cells [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has mostly been reported in immunocompromised patients receiving immunosuppressive drugs for hematologic malignancy [4], renal transplantation [5], rheumatoid arthritis [6], leprosy [7], and asthma [8]; however, there has been one report of a healthy, immunocompetent host [11], as shown in Table 2. Medicopsis romeroi has also reported in patients with type 2 diabetes mellitus who have poor glycemic control [9,10]. Since phagocytic activity is the main mechanism for anti-fungal infections [12], type 2 diabetes patients with hyperglycemic control have a significant decline in the phagocytic activity of peripheral blood mononuclear cells [13].…”
Section: Discussionmentioning
confidence: 99%
“…Two earlier reports on type 2 diabetes patients had similar settings, namely, the two patients were females aged around 50 years, had a blood sugar level above 400 g/dL, and came to hospital with a firm mass on one side of a foot. In each case, molecular diagnosis identified Medicopsis romeroi [9,10]. Both cases demonstrated clinical improvement by surgical incisional and drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient only had diabetes mellitus. To our knowledge, this is the second case of subcutaneous phaeohyphomycosis due to P. romeroi described in a diabetic patient ( Yadav et al, 2015 ).…”
Section: Discussionmentioning
confidence: 72%
“…In the genus Roussoella, there is one reported opportunistic pathogen, Roussoella percutanea (Ahmed et al, 2014). In the genus Pyrenochaeta, the strain Pyrenochaeta romeroi (Yadav et al, 2015;Kulkarni et al, 2016) is reported to cause subcutaneous phaeohyphomycosis in transplant or diabetes patients (Ya-dav et al, 2015;Kulkarni et al, 2016). Purpureocillium (Paecilomyces) lilacinum is also reported as an opportunistic pathogen (Luangsa-Ard et al, 2011).…”
Section: Microtiter Plate Screening With Pure Culturesmentioning
confidence: 99%